An investigation of the effect of hydrodynamic stress on the growth, morphology and metabolism of microorganisms - Illing, Suzanne (Centre for Bioprocess Engineering Research, 2016)
The cultivation of bacteria requires high levels of agitation and aeration to satisfy the mass transfer requirements of the cells. Associated with these conditions are turbulent forces which may act on the surfaces of the cells and be detrimental to their growth, metabolism and morphology. Reactor design and operation may require a compromise between the stress sensitivity and the mass transfer requirements of the .microbial system. In this project, the development of general predictive techniques to optimise the design and operation for stress sensitive microorganisms was sought. The effect of hydrodynamic stress on the growth, metabolism and morphology of Corynebacterium glutamicum (ATCC 13032) and Brevibacterium flavum (NRRL 114 75) was investigated in a stirred tank bioreactor in the absence of mass transfer limiting conditions. The results showed that hydrodynamic trauma had no effect on the growth and metabolism of the bacteria. Breakup of bacterial aggregates was however observed, the extent of which depended on the intensity of the hydrodynamic conditions. The extent of aggregate breakup was greater for Corynebacterium glutamicum. It was postulated that the bacteria were held together by a growth associated biomolecular adhesive. The kinetics and mechanism for Corynebacterium glutamicum aggregate breakup in the absence of a gaseous phase, were studied in a stirred tank reactor and capillary flowloop system. A model was developed to describe the rate of aggregate breakup caused by aggregate-turbulent eddy interactions in the impeller zone of the stirred tank reactor and in the wall region of the capillary, in the absence of air bubbles. It assumes that aggregate disruption is caused by the interaction with similarly sized eddies. The extent of aggregate breakup was a function of the magnitude of the turbulent force as well as the total duration of the force event. A similar model was developed to describe the rate of microbial cell death. The forces associated with turbulent eddies in the impeller zone of the stirred tank reactor were compared with those of collapsing air bubbles at the air medium interface. The results showed that both contributed to the total force acting on the cells.